Prematurity: epidemiology, perinatal morbidity and mortality. Prognosis and long term evolution - Oliveros, Miguel (2015)
Very low birth weight infants are below 1 500 g, have very immature organs, peculiar physiology, high morbidity and mortality and frequent sequelae. They need special nutrition and care. Along neurological problems they present chronic pulmonary disease, language delay, growth retardation, strabismus, deafness, attention deficit, herniae and sudden death syndrome diagnosed in the follow up.